The Information Security of Enterprises and Citizens' Security Context - Roman Jasek (Communications - Scientific letters of the University of Zilina, 2019)
The aim of the article to show the analogical procedures encountered while dealing with the security of a company or personal security. Security of Information Systems relates closely to modern-day life and the solution of crisis situations is but one part. It does not matter whether the reason of the crisis is the human factor (purposely or unpremeditated) or even a technical failure. All systems must be able to switch to reserves within real time in order to ensure process continuity. While this article is about systems in the economic (financial) field, the same rules apply in government crisis management at any level. Consequently, the rule of Crisis Management in contemporary society is essential.